A case study on Percetakan Nasional Malaysia Berhad (PNMB) of the evaluating financial performance on ratio analysis and common size financial statement analysis / Nur Firdaus Md Akhir @ Rosidan - Md Akhir @ Rosidan, Nur Firdaus (2011)
Financial statement analysis provides information to those interested in the financial condition and operating results of a company. When financial statement items are considered individually, they usually will have a limited significance. A better perspective is gained when comparisons are made with previous statements, other business and industry averages. The main purpose of conducting financial analysis is to measure profitability and solvency. A large part of financial analysis deals with the interrelationship between various pieces of information. Financial ratios are used to express many of these relationships. Almost all of the information needed to perform the analysis is found on the balance sheet, income statement, or statement of cash flow. (David Johnston, 2006). Financial statement analysis is an integral and important part of the broader field of business analysis. Financial statement analysis is the application of analytical tools and techniques to general-purpose financial statements and related data to derive estimates and inferences useful in business analysis. Financial statement analysis reduces reliance on hunches, guesses and intuition for business decisions. It decreases the uncertainty of business analysis. It does not lessen the need for expert judgment but, instead provides a systematic and effective basis for business analysis. (K.R. Subramanyam, John J. Wild, 2009). Such ratios are ways of comparing and investigating the relationships between different pieces of financial information. Using ratios eliminates the size problem because the size effectively divides out. We’re then left with percentages, multiples, or time periods. There is a problem in discussing financial ratio. Because a ratio is simply one number divided by another, and because there is substantial quantity of accounting numbers out there, there are a huge number of possible ratios we could examine. Everybody has a favourite. We will restrict ourselves to a representative sampling. (Stephen A. Ross, 2006) A variety of tools designed to fit specific needs available to help users analyze financial statements. (K.R. Subramanyam, John J. Wild 2009). The main method of analysis is ratio analysis. Besides the ratio analysis, the other methods are comparative financial statement analysis and common size financial statement analysis.